(untitled) (De Rebus Antiquis, 2021)
The aim of this work is to examine the question of the differences and similarities in the legislative treatment presented by Philo of Alexandria in De Specialibus Legibus, from the debate opened by modern researchers about the sources of the philonic legislation and, especially, to the influence received by the prohibition of the theft bía kaÁ¬ phanerÁ´s in De Specialibus Legibus IV 2. To this purpose, we will try to 1) review scholars’ interpretations of the question of differences and similarities between De Specialibus Legibus and Palestinian traditions and Greco-Roman; 2) study this issue in discussions of the law on the prohibition of theft bía kaÁ¬ phanerÁ´s; 3) propose an interpretation of this law in relation to the problem of tax collection in Roman Egypt by P. Lond. 3 1171 verso (c) and De Specialibus Legibus II 92-95 and III 159-163.